Biopsychosocial aspects in individuals with acute and chronic rotator cuff related shoulder pain: Classification based on a decision tree analysis - Haik M.N.* (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland.Biopsychosocial aspects seem to influence the clinical condition of rotator cuff related shoulder pain (RCRSP). However, traditional bivariate and linear analyses may not be sufficiently robust to capture the complex relationships among these aspects. This study determined which biopsychosocial aspects would better classify individuals with acute and chronic RCRSP and described how these aspects interact to create biopsychosocial phenotypes in individuals with acute and chronic RCRSP. Individuals with acute (<six months of pain, n = 15) and chronic (≥six months of pain, n = 38) RCRSP were included. Sociodemographic data, biological data related to general clinical health status, to shoulder clinical condition and to sensory function, and psychosocial data were collected. Outcomes were compared between groups and a decision tree was used to classify the individuals with acute and chronic RCRSP into different phenotypes hierarchically organized in nodes. Only conditioned pain modulation was different between the groups. However, the tree combined six biopsychosocial aspects to identify seven distinct phenotypes in individuals with RCRSP: three phenotypes of individuals with acute, and four with chronic RCRSP. While the majority of the individuals with chronic RCRSP have no other previous painful complaint besides the shoulder pain and low efficiency of endogenous pain modulation with no signs of biomechanical related pain, individuals with acute RCRSP are more likely to have preserved endogenous pain modulation and unilateral pain with signs of kinesiophobia.